The human face - Bates, Brian; Cleese, John. (New York, N.Y. : Dorling Kindersley Pub., 2001)
The fascinating story of our most familiar features. An intriguing and unique journey of self-discovery, exploring the evolutionary, social and psychological aspects of the face.
Introduction -- Origins -- Identity -- Expressions -- Beauty -- Vanity -- Fame -- Conclusion.
"Published to accompany the television series The human face, first broadcast on BBC-1 in 2001"--T.p. verso.
Includes bibliographical references (p. 234-237) and index.
Keywords: Facial expression; Face -- Psychological aspects; Physionomie; Visage -- Aspect psychologique